Promoting books and places: A study of adjectival modification in persuasion and description - Yli-Jokipii, Hilkka (HERMES - Journal of Language and Communication in Business, 2003)
This is a study of adjectival modification, that is the use of adjectives and adjectival participles, in the genres of book information and place description. Book information represents a genre with a subtle, covertly persuasive function, while place description is taken to have little or no persuasive force. The study starts out with a quantitative element, establishing lexical densities of the eight texts in the data. This is followed by qualitative analyses of the functions which adjectives have in the genres examined. Answers are sought to these primary questions: 1) What is the role of modifying adjectives in the lexical density of the texts analysed? 2) What discourse functions do these adjectives fulfil in the two genres? The conclusions of the study include: 1) High occurrence of modifying items does not automatically equal nominal style. 2) High occurrence of modifying items is not an automatic sign of high lexical density. 3) The frequent use of modifiers in non-fiction is not limited to persuasion, since adjectives are also frequent in the genre in which the descriptive function is foregrounded.